Metabolic syndrome is a sequela of radiation exposure in hypothalamic obesity among survivors of childhood brain tumors. (9th December 2018) - Cooksey, Raven; Wu, Susan Y; Klesse, Laura; Oden, Jon D; Bland, Ross E; Hodges, Joseph C; Gargan, Lynn; Vega, Gloria Lena; Bowers, Daniel C
Abstract : Survivors of childhood brain tumors may be at risk for early onset of metabolic syndrome, possibly secondary to surgery and/or radiation exposure. This study examines effects of radiation exposure to hypothalamus-pituitary-adrenal axis (HPA) on metabolic risk among survivors of childhood brain tumors. One hundred forty-two met inclusion criteria; 60 had tumor surgery plus radiation exposure (> 1 Gray (Gy)) to HPA. The second subgroup of 82 subjects had surgery only and were not exposed to radiation. Both subgroups had survived for approximately 5 years at the time of study. All had clinical evaluation, vital signs, anthropometry, measurement of body composition by dual X-ray absorptiometry and fasting laboratory assays (metabolic panel, insulin, C-peptide, insulin-like growth factor-1, leptin and adiponectin). Body composition data for both subgroups was compared with the National Health and Nutrition Survey (NHANES) subgroup of similar age, gender and body mass index. Cranial surgery was associated with obesity of similar severity in both subgroups. However, survivors exposed to radiation to the HPA also had increased visceral fat mass and high prevalence of growth hormone deficiency and metabolic syndrome. Fat mass alone did not explain the prevalence of the metabolic syndrome in radiation exposure subgroup. Other factors such as growth hormone deficiency may have contributed to metabolic risk. We conclude that prevalence of metabolic syndrome among subjects exposed to hypothalamic radiation was higher than expected from hypothalamic obesity alone. Radiation exposure may exert untoward endocrinopathies due to HPA exposure that worsens metabolic risk. Early screening for metabolic syndrome in this population is indicated.